Impact of Albizia Wood (Albizia Chinensis) Adsorbent on the Reduction of Pollutants and Copper in Industrial Wastewater - Yulia Sukmawardani; Siti Jualiah; Cucu Zenab Subarkah; Tri Wahyu Agustina; Ade Yeti Nuryantini; Ida Farida (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
This paper investigated the possibility of using mothball tree wood to absorb copper from industrial wastewater. The adsorbent is made from sawdust, activated with 3N H3PO4 for 24 hours to increase its porosity and surface area, and examined its morphology and microstructure by Scanning Electron Microscope (JEOL-6510A). Pollution abatement experiments were carried out with uncontrollable samples from these three original rivers contaminated by textile, laundry, and industrial revenues. Copper content was determined by Atomic Absorption Spectroscopy (AAS); as well as various parameters such as the dissolved oxygen (DO), BOD5,codconsumed nitrates nitrogen, TDS, and TSS measured. As a result of the adsorption process, a significant reduction of pollutants was achieved. The concentrations of copper in samples reduced to lower than measurable levels or became